Reduction in mobility and COVID-19 transmission - Pierre Nouvellet (Nature Portfolio, 2021)
Social distancing policies aiming to reduce COVID-19 transmission have been reflected in reductions in human mobility. Here, the authors show that reduced mobility is correlated with decreased transmission, but that this relationship weakened over time as social distancing measures were relaxed.